STUDI KASUS POLA ASUH ORANG TUA DAN PENYEBAB ANAK MENGALAMI SIBLING RIVALRY - Afini Freudwi Asri; Rima Aulia Rahmaniah; Winna Andini Handayani (Jurnal Education and Development, 2023)
Sibling rivalry is a phenomenon of jealousy of children to their siblings which is commonly found among the community, especially children who are still at an early age. The purpose of this study is to see how sibling rivalry behavior can occur, as well as to see the description of parenting patterns in early childhood who experience sibling rivalry in Tasikmalaya. This research is a qualitative descriptive study using a case study approach. This study was conducted on 3 parents who have early childhood who experience sibling rivalry behavior. The results showed that parenting given to early childhood who experienced sibling rivalry was permissive parenting, neglectful parenting, and authoritarian parenting. Meanwhile, the cause of sibling rivalry behavior arises because of differences in parental attitudes, birth order, gender, and age differences that are too short. From sibling rivalry behavior, substantive types of behavior appear, starting from quarrels between siblings, sibling's power attitude, and getting each other's parents' attention. Parenting advice given by parents to overcome sibling rivalry behavior in each child is that parents establish communication to carry out joint parenting and parents spend more time for children and be fair to all their children.